P14.29 Prediction of overall survival in patients with malignant glioma using dynamic O-(2-[18F]-fluoroethyl)-L-tyrosine PET. (6th September 2019) - Bauer, E K; Stoffels, G; Blau, T; Reifenberger, G; Werner, J M; Lohmann, P; Rapp, M; Fink, G R; Langen, K; Galldiks, N
Abstract: BACKGROUND: Characterization of gliomas according to the revised World Health Organization (WHO) classification of 2016 has gained major importance regarding prognostication. The present study aimed at exploring the prognostic value of dynamic O-(2-[18F]-fluoroethyl)-L-tyrosine (FET) PET in newly diagnosed and molecularly defined astrocytic high-grade glioma (HGG) of the WHO grades III or IV. MATERIAL AND METHODS: Before initiation of treatment, dynamic FET PET imaging was performed in patients with newly diagnosed glioblastoma (GBM) and anaplastic astrocytoma (AA). Static FET PET parameters such as maximum and mean tumor/brain ratios (TBRmax/mean), as well as the dynamic FET PET parameters time-to-peak (TTP) and slope, were obtained. The predictive ability of FET PET parameters was evaluated with regard to the overall survival (OS). Using ROC analyses, threshold values for FET PET parameters were obtained. Subsequently, univariate Kaplan-Meier and multivariate Cox regression survival analyses were performed to assess their predictive power for OS. RESULTS: Sixty patients (45 GBM, 15 AA) of two university centers were retrospectively identified. Patients with a methylated MGMT promoter as well as with an IDH mutation had a significantly longer OS (both P<0.001). Furthermore, ROC analysis revealed in IDH-wildtype HGG (n=45) that a TTP>25 minutes (AUC, 0.90; sensitivity, 90%; specificity, 87%; P<0.001) was highly prognostic for a longer OS (29 vs. 12 months; P<0.001). Besides a complete resection and a methylated MGMT promoter, TTP remained significant in the multivariate survival analysis (P=0.002, P=0.016, and P=0.003, respectively), indicating an independent predictor for OS. In contrast, both TBRmax and TBRmean were not prognostic (AUC, 0.37 and 0.32, respectively). CONCLUSION: Data suggest that within the subgroup of patients with newly diagnosed and untreated IDH-wildtype GBM and AA, dynamic FET PET additionally allows the identification of patients with an improved OS.